The Effect of Family Psychoeducation on Social Support among Congestive Heart Failure Patients - Niman, Susanti; Hamid, Achir Yani S; Yulia W, Ice (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
The prevalence of CHF is increasing every year. The impact of a psychosocial condition requiringcomprehensive treatment for CHF in all aspects. One contributing factor to success is the involvement ofthe family. Purpose: This study aimed to determine the differences of social support towards clients withCHF who were receiving family psychoeducation. Method: This study used a Quasi -experimental prepost test without a control group”. A sample of 25 respondents and sample retrieval techniques with apurposive sampling procedure. The instrument used was an ISSB questionnaire for measuring socialsupport. The intervention group was provided with family psychoeducation that performed 5 sessions.Result and conclusion: The finding this study showed was a significant change before and after the familysupport family psychoeducation (p-value 0.00<α). Characteristics of the family and the client is notassociated with social support. Family psychoeducation research way recommended developed in a publichospital.